Testosterone induces off-line perceptual learning - Wright, Nicholas D.; Edwards, Thomas; Fleming, Stephen M.; Dolan, Raymond J. (Psychopharmacologia, 2012)
Rationale Perceptual learning operates on distinct timescales. How different neuromodulatory systems impact on learning across these different timescales is poorly understood. Objectives Here, we test the causal impact of a novel influence on perceptual learning, the androgen hormone testosterone, across distinct timescales. Methods In a double-blind, placebo- controlled, cross-over study with testosterone, subjects undertook a simple contrast detection task during training sessions on two separate days. Results On placebo, there was no learning either within training sessions or between days, except for a fast, rapidly saturating, improvement early on each testing day. However, testosterone caused “off-line” learning, with no learning seen within training sessions, but a marked performance improvement over the days between sessions. This testosterone-induced learning occurred in the absence of changes in subjective confidence or introspective accuracy. Conclusions Our findings show that testosterone influences perceptual learning on a timescale consistent with an influence on “off-line” consolidation processes.